2000
DOI: 10.1180/002646100549085
|View full text |Cite
|
Sign up to set email alerts
|

Further study of the cation ordering in phengite 3T by neutron powder diffraction

Abstract: Phengite 3T (Dora-Maira massif, Italian western Alps), with chemical composition K 0.96 Na 0.01 Al 1.44 Mg 0.56 (Si 3.59 Al 0.41 )O 10 (OH) 2 has been investigated using powder neutron diffraction, at the ILL (Institut Laue-Langevin) Facility, on the D2B diffractometer. Data sets were collected at 293 and 873 K, and the present results are compared with those obtained previously using the time-of-flight (TOF) technique, on the same compound. In the octahedral sheet, Al tends to order into the M2 site, in accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Pavese et al [77][78][79] have conducted many experimental studies of the 2M 1 and 3T polytypes of phengite. Much of their work suggests a low degree of octahedral cation order in both polytypes, but by contrast, their most recent investigation of a different natural phengite 3T sample from that previously studied, concluded that the sample exhibited both octahedral and tetrahedral order.…”
Section: Review Wwwq-chemorgmentioning
confidence: 99%
“…Pavese et al [77][78][79] have conducted many experimental studies of the 2M 1 and 3T polytypes of phengite. Much of their work suggests a low degree of octahedral cation order in both polytypes, but by contrast, their most recent investigation of a different natural phengite 3T sample from that previously studied, concluded that the sample exhibited both octahedral and tetrahedral order.…”
Section: Review Wwwq-chemorgmentioning
confidence: 99%
“…Neutron diffraction provides a powerful structural adjunct to FTIR studies of micas (e.g. Pavese et al, 2000). Here we use both in situ high-temperature FTIR and crystallographic data from refinement of the neutron diffraction experiments previously reported in Mookherjee et al (2001) to shed light on the behaviour of the interlayer and basal oxygens of mica.…”
mentioning
confidence: 99%
“…Numerous crystallographic data have been published after Sassi et al (1994), showing that HP favors cation ordering and stabilizes 3T stacking (Pavese et al 1997(Pavese et al , 1999a(Pavese et al , 1999b(Pavese et al , 2000(Pavese et al , 2001(Pavese et al , 2003Brigatti et al 2005;Curetti et al 2006;Gatta et al 2009, and references therein), and Gatta et al (2010) find evidence supporting a better stabilization of 3T stacking than 2M 1 . However, experimental studies on phengite are limited with respect to polytype formation and crystallization pressure (Smyth et al 2000), although synthetic phengites may not be representative of equilibrium conditions (Schmidt et al 2001;Curetti et al 2008).…”
Section: Introduction and State Of Artmentioning
confidence: 95%